Enabling Innovation in The Philippine Rice Industry: The Roles and Key-Capabilities of Innovation Intermediaries - Kevin Christopher Go (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2022)
The innovation studies literature finds that innovation intermediaries or innovation-enabling organizations perform roles that promote knowledge transfer, organizational development, and network collaboration. Furthermore, these organizations require building necessary key-capabilities that allow them to conduct these roles more successfully. However, a gap remains in understanding how intermediaries perform their roles and develop key-capabilities as global value chains and innovation systems interact, especially in agri-food business industries. This study chooses the Philippine rice industry as a case. It shows how innovation intermediaries in the industry support the upgrading, participation, and innovation of their stakeholders to compete against cheaper rice produced abroad. It provides several policy and management implications for maximizing the role performance and key-capability building of innovation intermediaries in agri-food business industries. This article is part of a more extensive dissertation on how innovation intermediaries in agri-food business industries perform roles and build key-capabilities as their organization types, value chain segment participation, and industry’s market orientation vary.